Assessing welfare accounts - Stefan Fölster; Robert Gidehag; Jonathan Michael Orszag; Dennis J. Snower (Institute for the Study of Labor (IZA), 2002)
The paper examines the possible effects of introducing a large-scale welfare reform in Sweden, namely, the introduction of comprehensive welfare accounts. Under this policy, individuals make mandatory contributions to accounts, which they can top up with voluntary contributions. In return, individuals? welfare benefits are paid from their accounts. The paper uses a large panel of individual income data to examine how the adoption of universal welfare accounts may affect economic activity. We find that this policy could be designed so as to reduce social insurance expenditure considerably, improve the incentives to work and save, all with relatively small redistributive impact.
Keywords: H51; H52; H53; H55; H11; H21; H23; 330; welfare accounts; social insurance; taxes; welfare state benefits; welfare reform; Soziale Sicherung; Sozialversicherung; Sozialreform; Sozialversicherungsbeitrag; Sparen; Schweden